Pengaruh Literasi Keuangan, Financial Tekhnologi Dan Gaya Hidup Terhadap Perilaku Pengelolaan Keuangan - Rosa Norita; Mahirun (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
This study aims to test and analyze the influence of financial literacy, financial technology and lifestyle on financial management behavior. The population in this study is KSPPS BMT Bahtera employees, and sampling is done using purposive sampling techniques. A sample of 100 employees was obtained. To test the influence of the indepent variable on the independent variable, multiple linear regression analysis was used in the SPSS program. The test results found that Financial Literacy had a positive and significant effect on financial management behavior, while lifestyle had a negative and significant effect on financial management behavior. The variable that does not affect financial management behavior is financial technology.